Recitativo, Ária e Fuga para violoncelo e orquestra de cordas de José Siqueira: dimensões estéticas e interpretativas - Santos, Roberta Regina dos (2016)
Written during Siqueira‟s third compositional period the Recitativo, Ária e Fuga para violoncelo e orquestra de cordas (1972) combines neo-baroque elements with the sounds of northeastern Brazil. This research aims to present an approach about the aesthetic and interpretative dimensions of the work. Formulated from an extremely compact structure, in three movements, whose total duration does not reach nine minutes, the composer uses a series of 12 sounds generated by the superposition of ascending which is the fourths, main elements of the Recitativo. The Ária is marked by a chromatic bass line that continues throughout the movement. The work ends with a fugue whose subject and counter-subject are structured from motivic elements originated from previous movements, whose production comes from modal scales. This combination of compositional techniques comprise to a neo-baroque structure that can be seen as an expansion of the French Overture, as discussed in the text. This study is complemented with the edition of the work in more than one version edition of orchestral score, a piano reduction, and a performance edition which includes fingering and bowing suggestions that are defined by interpretative concepts originated from the analysis presented in this study as well as from the perfomances of the work during the Master‟s Program.